On the Eringen model for nematic liquid crystals - Chechkin, Gregory A.; Ratiu, Tudor S.; Romanov, Maxim S. (Comptes Rendus. Mécanique, 2021)
We introduce the three-dimensional Eringen system of equations for the nematodynamics of liquid crystals, announce the short time existence and uniqueness of strong solutions for the one-dimensional problem in the periodic case, and show the continuous dependence of the solution on the initial data.